Developing effective workforce training to support the long‐term care of older adults: A review of reviews. (5th July 2022) - Newbould, Louise; Samsi, Kritika; Wilberforce, Mark
Abstract: This review of reviews aimed to identify and synthesise evidence to support the design of learning interventions for non‐registered practitioners supporting older people in long‐term care (people's own homes, hospices or residential/nursing care). Our objectives were to inform the analysis part of the Analysis, Design, Development Implementation and Evaluation framework by finding evidence on the following five components of learning: content, format (teaching strategies and resources/media), structure, contextual factors (barriers and enablers) and measures used when monitoring the effectives of learning. Databases searched included Pro‐quest (ASSIA), Scopus, Ovid (PsycINFO, Medline, Embase and Social Policy and Practice), SCIE Online and Cochrane Reviews and reference searching, with the last search being conducted in April 2021. Fifteen papers were identified as eligible for inclusion. Most of the interventions aimed to improve dementia care ( n = 10), with others exploring LGBT+ competency ( n = 2), or other forms of professional development ( n = 3). Common features of effective learning included a multifaceted approach, with in‐practice learning being blended with additional implementation strategies (e.g. supervision) and didactic learning/worksheets. An important contextual factor was working within an organisational culture which supported shared learning and reflection. This may also help encourage engagement with training, where staff are unwilling to attend if it may compromise care delivery. Future research should focus on the characteristics of trainers and the structure of learning, with more research being needed in in mental and physical morbidities outside the remit of dementia to improve the overall quality of the social care workforce.